(untitled) (Window of Public Health Journal, 2026)
According to Law Number 25 of 2009, good public service is essential for effective governance and should inspire a sense of purpose among researchers, policymakers, and managers committed to improving government functions. However, during implementation, various complaints regarding BPJS of Employment services are still being reported. An investigation by the Indonesian Ombudsman (Ombudsman) found maladministration in BPJS of Employment services, including in Makassar City, such as long wait times, difficulties in the claims process, and a lack of clear information for participants. This condition is also reflected in customer reviews via Google Reviews, which indicate a low level of public satisfaction with BPJS of Employment services in Makassar. One factor suspected of influencing service quality is employee intrinsic motivation, as strong motivation is expected to improve employee performance. This study aims to determine the relationship between intrinsic motivation and employee performance at the BPJS of Employment Office in Makassar City. This research is a quantitative study employing a cross-sectional approach, focusing on all 30 employees at the BPJS of Employment Office in Makassar City. The entire population was sampled using a total sampling technique. Data collection involved questionnaires, and analysis was conducted using a chi-square test at α = 0.05 to determine relationships between variables. The analysis indicated no significant relationship between intrinsic motivation and employee performance at the Makassar City BPJS of Employment Office (p-value = 0.193 > α = 0.05). These findings suggest that enhancing intrinsic motivation alone may not directly improve performance, highlighting the need for comprehensive strategies to boost service quality and public satisfaction. This study recommends that the Makassar City BPJS of Employment Office continue to improve service quality through more informative, responsive, and participant-focused communication. Such efforts can help build trust and motivate stakeholders to work together to minimize public complaints about the services provided.